Stolen Life's Poetic Revolt. (June 2019) - Odysseos, Louiza
Joining the discussion of revolution and resistance in world politics, this article puts forward the idea of poetic revolt as a necessary companion to these terms, one which centres attention on the ongoing reverberations of transatlantic slavery – what have been called its 'afterlives' (Saidiya Hartman, Édouard Glissant). Engaging with contributions to poetics, black studies and black feminist thought, it first develops a theoretical orientation of the ongoingness of slavery as a 'grammar of captivity' (Hortense Spillers) that 'wake work', a term proposed by Christina Sharpe, aims to disrupt. The article calls for methodological attention to the fugitive and wayward arts and acts of living, that is, what Sylvia Wynter and Fred Moten call the 'sociopoetic' practices of enslaved and legally-emancipated populations to illuminate the simultaneity and entanglement of structuring violence and poetic revolt. Second, drawing on Spillers' scholarship on homiletics – the study of and participation in sermons – in particular United States contexts, it identifies and discusses three aspects of poetic revolt: 'fabulation', world-making otherwise and resignification, through which such communities developed a critical and insurgent posture aimed at rupturing this grammar of captivity and at forging critical, futurally-oriented sociabilities. Third, in conclusion, it discusses the links of poetic revolt, in its specificity in Atlantic slavery, to wider systemic critique. Pluralising our thinking on revolution and resistance, poetic revolt, it argues, is best seen as a critical meditation on futurity.